Perlindungan Konsumen Terhadap Produk Yang Telah Mencantumkan Label Halal Sebelum Memiliki Sertifikat Halal Berdasarkan Undang-Undang Nomor 8 tahun 1999 Tentang Perlindungan Konsumen - Fadhilla Wulandari; Nuzul Rahmayani; Syuryani (Journal of Indonesian Comparative of Syari'ah Law, 2023)
A halal certificate is a statement letter on the halalness of a product issued by an authorized institution whose legitimacy has been ascertained, the large number of frauds committed by business actors for counterfeiting the halalness of their products causes threats to the rights that consumers should receive. As a form of protection for consumer rights, the government has established provisions that are currently in effect, namely Law no. 08 of 1999 concerning Consumer Protection. With the existence of this consumer protection law, it will have an impact on the welfare and peace of Muslim communities wherever they are. The results of the research are expected to raise awareness among business actors how important halal certificates and halal labels are for Muslims and non-Muslims alike. Based on this research, it can be concluded how the law regarding consumer protection regulates and protects consumers who feel disadvantaged by the actions of irresponsible business actors who only think about big profits without thinking about what impact they will get. The approach method used in this study is a normative approach, a normative approach is an approach that is carried out by observing problems by analyzing norms, regulations that apply, and based on circulating news. Looking at the rules provided by law regarding consumer protection, how is the responsibility that should be given by someone as a business actor for losses received by consumers for the products they distribute and what actions consumers must take to be careful in reading and listening to information regarding the halalness of the product they will consume or use.